Współczesne studia nad Diodorem Sycylijskim = Contemporary studies on Diodorus Siculus - Dudziński, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to present the Polish reader with a brief outline of the current discussions in the field of the studies of Diodorus Siculus` "Bibliotheke Historike" - one of the most important sources for studying ancient history. In the first part, the article discusses the main publications in the fields - including especially monographs on Dodorus and his work, editions and translations, and commentaries to individual books or groups of books.
Keywords: Diodor Sycylijski (historyk grecki; ok. 80 p.n.e. - ok. 20 p.n.e.); historiografia grecka; starożytna Grecja; historia starożytna; Diodorus Siculus; Greek historiography; ancient Greece; Ancient history